سیاسەتی چاکسازیی و کرانەوە ی چین و کاریگەریی لەسەر پەیوەندییەکانی چین – سۆڤیێت (١٩٧٨-١٩٩٢) - سەعید, پ.ی.د.هیوا عەزیز; توفیق, م.ی. ئەیوب ظاهر (Sulaimani Journal for Humanities, 2023)
In general, Sino-Soviet relations from 1978 to 1992 were expected to change, moving from open hostility to a pragmatic approach of mutual reassurance, mutual benefit and neighborhood rights, characterized by the participation of diplomatic and economic mechanisms and increased cultural exchange. This study attempts to explore the nature and spheres of Sino-Soviet relations through analytical methods, while identifying the obstacles and motives that played a role in these relations. As a conclusion of this study, although Sino -Soviet relations have recorded a complex and tense relationship in their history and the region, but the needs of both sides played a role in the development, continuity and strengthening of relations, they were regional and international, making the rapprochement of these two forces a cultural necessity of the period. So that they can each continue their position, continuity and the process of reform and development.
Keywords: Relations; SinoSoviet; China; Reform and openingup policy